THE EFFECT OF ECONOMICS VALUE-ADDED, MARKET VALUE-ADDED, TOTAL ASSET RATIO, AND PRICE EARNINGS RATIO ON STOCK RETURN - Willy Poltak Silitonga; Rizky Alika Ramadhani; Ridho Nugroho (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2018)
This study is to analyze the effect of economic value added, market value added, total assets turn over and price earning ratio to stock returns. The multiple linear regression analysis used to identify the effect of independent variables on the dependent variable. The sample was obtained from the consumer goods sector listed on the Indonesia Stock Exchange. The data covers three years from 2015 to 2017. The results of this study indicate total asset turnover (TATO) and price earnings ratio (PER) have a significant effect on stock return whereas the other variable economics value added and market value added is insignificant on stock return.